Differences of protein expression profiles, KRAS and BRAF mutation, and prognosis in right-sided colon, left-sided colon and rectal cancer - Xian Hua Gao (Nature Portfolio, 2017)
Abstract To compare protein expression levels, gene mutation and survival among Right-Sided Colon Cancer (RSCC), Left-Sided Colon Cancer (LSCC) and rectal cancer patients, 57 cases of RSCC, 87 LSCC and 145 rectal cancer patients were included retrospectively. Our results demonstrated significant differences existed among RSCC, LSCC and rectal cancer regarding tumor diameter, differentiation, invasion depth and TNM stage. No significant difference was identified in expression levels of MLH1, MSH2, MSH6, PMS2, β-Tubulin III, P53, Ki67 and TOPIIα, and gene mutation of KRAS and BRAF among three groups. Progression Free Survival (PFS) of RSCC was significantly lower than that of LRCC and rectal cancer. In univariate analyses, RSCC, preoperative chemoradiotherapy, poor differentiation, advanced TNM stage, elevated serum CEA and CA19-9 level, tumor deposit, perineural and vascular invasion were found to be predictive factors of shorter PFS. In multivariate analyses, only differentiation and TNM stages were found to be independent predictors of PFS. In conclusion, compared with LSCC and rectal cancer, RSCC has larger tumor size, poor differentiation, advanced TNM stage and shorter survival. The shorter survival in RSCC might be attributed to the advanced tumor stage caused by its inherent position feature of proximal colon rather than genetic difference.